Modifikasi Tata Rias Pengantin Giri Kedhaton Konsep Syar'i Sebagai Upaya Pelestarian Budaya Lokal Kota Gresik - Noviyani, Rista Ema Noviyani; Sri Dwiyanti; Dewi Lutfiati; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2026)
The Giri Kedhaton bridal makeup from Gresik is facing extinction, and efforts to preserve it are urgently needed. This research was conducted by modifying the Giri Kedhaton bridal makeup as an effort to preserve Gresik's local culture. The objectives of this research are: 1) to realize the design of modified Giri Kedhaton bridal makeup with a syar’i concept, 2) to realize the modification of Giri Kedhaton bridal makeup with a syar’i concept, 3) to understand the responses of the people of Gresik city as respondents to the results of the modification of Giri Kedhaton bridal makeup with a syar’i concept. This research is a descriptive study using qualitative methods. The study was conducted using the procedure of developing works of art. The object of this research is the modified bridal makeup of Giri Kedhaton with a syari concept. The subjects of this research are 5 sources and 40 respondents who are residents of Gresik city. This research was conducted using data collection techniques including observation, interviews, and documentation. The research uses data analysis techniques such as data reduction, data presentation, and verification. The results of this research are; 1) the design of the modified bridal makeup of Giri Kedhaton. The selected design is the one with the highest value from the three design options, which is design 2. The theme of the modified bridal makeup of Giri Kedhaton is in line with the syari concept, which is modern minimalist. The use of accents, materials, and colors is adjusted to a more modern and minimalist theme. 2) The results of the modified bridal makeup of Giri Kedhaton. The result of the modification is counted to be 29.99% of the overall framework. 3) The response of the people of Gresik regarding the results of the modification. The assessment from respondents resulted in a percentage of 87.1%, which is categorized as Very Good (according to the assessment criteria by Sugiono, 2012; 143). The results of the modification also received good evaluation feedback from observers and research sources. Thus, the modification is declared successful, and the modification of the Giri Kedhaton bridal makeup in the syar’i concept can be used by brides in wedding events. The results of the modification can also serve as a reference for the exploration of Giri Kedhaton bridal makeup by bridal makeup artists in Gresik city. Therefore, this exploration can be one of the efforts to preserve the traditional bridal makeup of Gresik.